(untitled) (Palíndromo, 2023)
Based on a set of engravings edited by Jacques Callot, one of the series of engravings by Francisco Goya and Editions and respective publications in local newspapers by Honoré Daumier and José Guadalupe Posada, this article intends to discuss the respective publications of the artists as aesthetic and/or political uprisings. To do so, we take at first the assumptions theorized by Susan Sontag in her work Regarding the Pain of Others and the cultural analyzes studied by Octavio Paz in The Labyrinth of Solitude, as well as in the essay The historical dossier of Apu-Mallq’u by Jorge Llaguno. It is also supported by the more in-depth studies of Rafael Barajas Duran on Posada’s work and the maxims analyzed by Georges Didi-Huberman in Levantes.